Team Teaching: Across the Disciplines, Across the Academy - James Rhem Kathryn M. Plank (Stylus Publishing, 2011)
For those considering adopting team teaching, or interested in reviewing their own practice, this book offers an overview of this pedagogy, its challenges and rewards, and a rich range of examples in which teachers present and reflect upon their approaches. The interaction of two teachers both the intellectual interaction involved in the design of the course, and the pedagogical interaction in the teaching of the course creates a dynamic environment that reflects the way scholars make meaning of the world. The process naturally breaks down the teacher-centered classroom by creating a scholarly community in which teachers and students work together to understand important ideas, and where students don t just learn content, but begin to understand how knowledge is constructed, grasp the connections between disciplines as well as their different perspectives, see greater coherence in the curriculum, and appreciate how having more than one teacher in the classroom leads naturally to dialogue and active learning.Each of the five examples in this book shares the story of a course at a different institution, and each is designed to reflect a number of different variables in team-taught courses. They represent courses in a variety of different disciplines, including the sciences, social sciences, humanities, and the arts; and at a range of levels, from first-year seminars to graduate courses. They also illustrate a number of different models for instructional teams, such as faculty from the same disciplines, from related disciplines, from two very different disciplines, from different institutions, and one pairing of a faculty member and a staff member. This book provides insight into the impact of team teaching on student learning and on faculty development. It also addresses the challenges, both pedagogical an administrative, that need to be addressed for team teaching to be effective."
Keywords: Education